1995
DOI: 10.1111/j.1399-3054.1995.tb05121.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of two types of β‐cyanoalanine synthase in germinating seeds and their responses to ethylene

Abstract: The presence of two types of /^-cyanoalanine synfhase in germinating seeds and fheir responses to ethylene. -Physiol. Plant. 93: 71.3-718.Germinafine seeds of many species contain fwo fypes of /i-cyanoalanine synthase (CAS. EC 4.4.1.9) thaf conveii HCN fo /?-cyanoa'lanine. One is cyfoplasmic CAS (cyt-C.AS), which is precipitated by 50 lo 609r (NHai^SO^ and has a pH optimum of 10.5. Cvtoplasmic C.^S is present at high levels in dry seed and its activity does nof increase during imbibition. The activity ot cyt-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
(3 reference statements)
0
23
0
Order By: Relevance
“…Eighty percent of the total cytosolic CAS activity is precipitated by 40-70% saturation with (NH 4 ) 2 SO 4 ; the solubilized mitochondrial CAS activity is precipitated at 50-80% saturation (data not shown). The apparent optimum pH of each CAS activity differed, with the former at 10.5 and the latter at 9.5 (Hasegawa et al 1995b). Moreover, the two CAS activities were clearly separated by non-denaturing PAGE.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Eighty percent of the total cytosolic CAS activity is precipitated by 40-70% saturation with (NH 4 ) 2 SO 4 ; the solubilized mitochondrial CAS activity is precipitated at 50-80% saturation (data not shown). The apparent optimum pH of each CAS activity differed, with the former at 10.5 and the latter at 9.5 (Hasegawa et al 1995b). Moreover, the two CAS activities were clearly separated by non-denaturing PAGE.…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, the mitochondrial CAS activity was divided into two bands, one of which appeared on a gel at a position similar to that of the cytosolic one (compare lane 1 and 4). In a previous paper, we reported that the CAS activity of cocklebur seeds was increased by ethylene (Hasegawa et al 1995b). This promotion by ethylene was also indicated on the gels by the different strengths of the staining activity (compare lanes 1 and 4 with lanes 2 and 3).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The enzyme from White birch, Betula verrucosa, was reported as a 38 Kd homodimer (Vahala et al, 2003). In summary, b-CAS has been found to exist in two molecular forms: a 52 Kd homomer and a homodimer with subunit sizes of 28-30 Kd (Hendrickson and Conn, 1969;Ikegami et al, 1988a, b;Hasegawa et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…b-CAS has also been found to exist in two molecular forms: a 52 Kd homomer and a homodimer with subunit sizes of 28-30 Kd (Hendrickson and Conn, 1969;Ikegami et al, 1988a, b;Hasegawa et al, 1995). Another enzyme, cysteine synthase (O-acetylserine (thiol) lyase; CS or O-ASTL; EC 4.2.99.8), which exists in three isofroms: cytosolic (cysteine synthase A), chloroplastic (cysteine synthase B) and mitochondrial cysteine synthases, has been found to be involved in cyanide detoxification alongside b-CAS in higher plants such as in spinach and in Arabidopsis Hawkesford, 1998, 2000).…”
Section: Introductionmentioning
confidence: 95%